MODERN APPROACHES TO THE ORGANIZATION OF FINANCIAL SUPPLY OF THE ARMED FORCES OF THE KYRGYZ REPUBLIC - R. Sh. Bekishov (Вестник университета)
The article performs an analytical review on the issues of reforms in the state structure of the Kyrgyz Republic and its military organization. The paper considers military reform as a necessary component of political and socio-economic reforms, one of the determining conditions for their success, an effective factor in ensuring the defense and security of Kyrgyzstan, its active and constructive role in the modern world. The author notes the necessity, from the point of view of the defense interests of Kyrgyzstan, in the development and adoption of fundamentally new methods of organizing the financial support of the Armed Forces of the Kyrgyz Republic. At the same time, the created mechanism of the organization should be aimed, first of all, at optimizing the size and structure of the Armed Forces, their compliance with the financial, economic, scientific, technical and other capabilities of the country to ensure its military security with the least expenditure of resources.